Pengaruh Model Cooperative Integrated Reading and Composition (CIRC) Berbantuan Aplikasi Riri dalam Meningkatkan Keterampilan Membaca Pemahaman Siswa Kelas IV Sekolah Dasar - Reygina Ekana Putri; Arifin Ahmad; Yuni Indriyani (Mataram University, 2026)
This study was motivated by the low reading comprehension skills of fourth-grade elementary school students. It aimed to: (1) describe the learning process using the Cooperative Integrated Reading and Composition (CIRC) model assisted by the Riri Interactive Children's Story application, (2) determine the differences in reading comprehension skills between students who learned through the CIRC model assisted by the Riri application and those who received conventional instruction, and (3) examine the effect of the CIRC model assisted by the Riri application on students' reading comprehension skills. This study employed a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. The participants were fourth-grade students of SDN 009 Cikadut, consisting of an experimental class and a control class. Data were collected through tests, observations, and documentation and analyzed using descriptive and inferential statistics, including normality, homogeneity, Independent Samples t-test, N-Gain, and Effect Size analyses. The results showed that teacher and student activities in the experimental class improved consistently during four learning sessions. The average score increased from 68.39 on the pretest to 82.71 on the posttest in the experimental class, while the control class improved from 68.80 to 74.88. The Independent Samples t-test revealed a significant difference between the two groups (Sig. = 0.029 < 0.05). The experimental class also achieved a higher N-Gain score (0.41) than the control class (0.14). Furthermore, the Effect Size value of 0.598 indicated a large effect of the CIRC model assisted by the Riri application on students' reading comprehension skills. Therefore, the Cooperative Integrated Reading and Composition (CIRC) model assisted by the Riri Interactive Children's Story application is effective in improving elementary school students' reading comprehension skills.